Lives in the law - Douglas, Lawrence; Sarat, Austin; Umphrey, Martha Merrill (Amherst series in law, jurisprudence, and social thought., 2002)
Examines how the lives of individuals, social groups, and nations are fashioned by their engagement with the law.